Delayed elimination communication on the prevalence of children's bladder and bowel dysfunction - Peng Chao Xu; Yi He Wang; Qing Jun Meng; Yi Bo Wen; Jing Yang; Xi Zheng Wang; Yan Chen; Yu Lin He; Qing Wei Wang; Yan Wang; Lin Gang Cui; Jennifer D. Sihoe; et al. (Scientific Reports, 2021)
Abstract To determine the prevalence of bladder and bowel dysfunction (BBD) and its relationship with delayed elimination communication (EC) in children. A cross-sectional study was carried out in kindergartens and primary schools in mainland China. A total of 10,166 children ranging from 4 to 10 years old were included. A total of 10,166 valid questionnaires were collected, and 409 children were diagnosed with BBD. The overall prevalence was 4.02% (409/10,166) and decreased with age, from 6.19% at age 4 to 1.96% at age 10. With the prolonged use of disposable diapers (DDs), the commencement of usage of EC in a child was significantly put off or delayed by parents, and the prevalence of BBD amongst these children increased (P < 0.001). The prevalence of BBD among children who stopped using DDs within the first 12 months and after more than 24 months was 2.79% and 4.38% respectively. Additionally, the prevalence among children who started EC within 12 months after birth and those who never engaged in EC was 1.36% and 15.71% respectively. Early introduction of EC and weaning of DD usage has a positive correlation with lower prevalence of BBD in children in China.